Diabetic Foot: A Reality in Mexico - Sanciprián, Rafael Martínez; Navarro, Gabriel Hafner Vázquez; Flores, Nicole López; Ocampo, Said Uriel Martínez; Domínguez, Octavio Orduña; Avila, Juan Antonio Juárez; Suárez, Ivonne Alondra León; Hernández, José Luis García; Sánchez, Morelos Adolfo García (British Journal of Healthcare and Medical Research, 2026)
Introduction: Diabetes mellitus is a disease with a group of metabolic alterations that is characterized by chronic hyperglycemia, which is caused by a defect in the secretion of insulin, to a defect in its action. Method: Retrospective, longitudinal, observational and descriptive multicenter study in three hospitals, with descriptive statistical results/analyzing the national and international medical literature. Results: A total of 1,195 patients, 711 are men (59.49%), 484 women (40.5%). Age range from 16 to 79 average of 51 years. The most frequent injury is trauma, mostly Wagner 5, and the treatment is supracondylar amputation. Discussion: The common and severe arterial disease of the lower extremities of microvascular atherosclerotic origin of type 2 diabetes mellitus, adding the infection and Charcot's deformity, causes the diabetic foot combo in the lower extremities, ulcers and even amputation, which increases the disability rate and the mortality rate of patients. Conclusions: Patients in Mexico who suffer from "diabetic foot" are unlikely to be a priority of the public health system, since their diagnosis and treatment are always in basic and stunted conditions. Without resources and supplies, without a public health policy or consensus on treatment and comprehensive rehabilitation.